Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Driver Grab-Bike - Muhammad Abil; Noor Rahmini (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
The purpose of this study is, (1) To find out how the characteristics of Grabbike drivers in Banjarmasin City. (2) To find out whether the type of service, frequency of delivery, and age influence the income of Grabbike drivers in Banjarmasin City. (3) To find out which factor is the most dominant influence on the income of Grabbike drivers in Banjarmasin City.This type of research uses quantitative descriptive methods by collecting data using Primary Data. Independent variables or independent variables in this study include service type (x1), delivery frequency (x2), and age (x3), and the dependent variable or dependent variable in this study is Grab-bike Driver Income. This research was conducted in Banjarmasin City precisely in January 2020. The data collection method used purposive sampling combined with accidental sampling through questionnaires, interviews, literature studies, and documentation. Data Analysis Techniques use the form of econometrics by regressing existing variables using Multiple Linear Regression analysis, which will involve more than one predictor or independent variable and will also use the OLS method to test all independent variables on the dependent variable.The conclusions of this study are 1.a) Based on the age characteristics of the respondents, it shows that respondents aged between 21-30 years were the most dominant, as many as 16 respondents with a percentage of 53.33%. b) Based on the gender characteristics of the respondents, it shows that all respondents totaling 30 people are male with a percentage of 100%. c) Based on the respondents' education level characteristics, it shows that respondents who graduated from high school were the most dominant, as many as 24 people with a percentage of 80% 20 people with a percentage of 66.67%. e) Based on the table of income characteristics of respondents, it shows that respondents who earn more than 3 million are the most dominant, as many as 21 people with a percentage of 70%. 2. The delivery frequency variable has a positive and significant effect on the income of grab bike drivers in Banjarmasin. In contrast, the service type and age variables do not have a positive and not significant effect on the income of grab bike drivers in Banjarmasin. 3. The delivery frequency variable has the most dominant influence on the income of grab bike drivers in Banjarmasin City.